Scarf-related hangman's fracture: A case report - Chiu, C.K.; Chan, C.Y.W.; Saw, L.B.; Kwan, Mun Keong (2010)
Background: Injury to the cervical spine due to a scarf-associated accident has not been reported in the literature. We present a case of a hangman's fracture in a 43-year-old woman that resulted from a scarf-related injury as a consequence of a motor vehicle accident. Purpose: To identify the mechanism of a scarf-related injury causing Hangman's fracture. Case Report: A 43-year-old woman was involved in a motor vehicle accident. She was wearing a scarf, which is a common clothing accessory for women in Malaysia. The scarf was violently torn off her head during the injury, causing a type I hangman's fracture. A halo vest for a total period of 3 months was applied. Conclusion: A scarf-related injury can cause an injury that resembles judicial hanging, leading to a traumatic spondylolisthesis of the axis. Careful evaluation of the cervical spine radiographs is crucial as occult fracture of the axis can be missed.